Non-Incorporation of the Principle of Non-Refoulement in the Chilean Immigration and Aliens Law - Rioseco Vallejos, Valentina (Serikat Pengajar Hak Asasi Manusia Indonesia, 2023)
This paper critically analyses the non-incorporation of the principle of non-refoulement in the Chilean Immigration and Aliens Law 21.325 of 20 April 2021. It was published in the context of migratory pressures within the Latin American region, deriving mainly from the Venezuelan socio-political crisis. It was also published after the recommendations given by the Committee on the Protection of the Rights of All Migrant Workers and Members of Their Families (CMW) in the last two periodic reviews of 2011 and 2021 to update the previous version dictated during the Pinochet dictatorship. As a state party to the core international human rights treaties and the American Convention on Human Rights, an urgent claim existed in Chile to adapt its migration law. Following a heated debate in 2019, the parliament eliminated the recognition of the principle of nonrefoulement contained in the draft law arguing it was already recognised in refugee legislation. Instead, they identified a ‘complementary protection’. This paper examines whether this decision breaches human rights standards, particularly the obligation to adopt legislative measures to give effect to the principle of non-refoulement. It begins by analysing the principle of non-refoulement in international refugee law. Then, it turns into identifying the human rights obligations emanating from the principle of non-refoulement. Finally, the paper applies this standard to law 21.325. The paper concludes that not incorporating the principle of non-refoulement into law 21.325 constitutes a breach of Chile’s human rights obligations, facing the risk of incurring international responsibility.